Stad en migratie in de literatuur - Eeckhout, Bart; Joosen, Vanessa; Sepp, Arvi; Eeckhout, Bart; Joosen, Vanessa; Sepp, Arvi (Gent Academia Press, 2016)
Urbanity and migration are considered to be two basic components in definitions of modernity. They force us to reflect on how the boundaries between the local and the global are determined and surpassed. Often this results in politically charged discussions about transnationality and national identity, monolingualism and multilingualism, inclusion and exclusion. The contributions to this issue of CLW demonstrate that literature can play a significant role in this debate. The authors highlight the representation of city and migration in a wide variety of novels published in Dutch, English, German, Spanish and French with a particular interest in political commitment.
Dutch; Flemish
Keywords: United Kingdom, Great Britain; c 1800 to c 1900; 20th century; Literature: history & criticism; Literary theory; Literary studies: fiction, novelists & prose writers; Poverty & unemployment; Housing & homelessness; Migration, immigration & emigration; Urban communities; Jewish studies; Belgium; France; Germany; USA; Argentina; Chile; English; Dutch; literary criticism; literary theory; urban literature; migration